Determinasi Bauran Pemasaran: Analisis Peran Daya Beli Konsumen, Pesaing, Perilaku Konsumen dan Demografi Konsumen - Fitria Ariyani; Josua Panatap Soehaditama; Sonya Sidjabat; Nunung Ayu Sofiati (Efi); Yosi Pahala (BADAN PENERBIT STIEPARI PRESS, 2025)
This literature study aims to develop a hypothesis regarding the influence between variables that can be used for further research in the scope of marketing management. The research article on determining the marketing mix: analysis of consumer purchasing power, competitors, consumer behavior, and consumer demographics is a scientific literature article in the field of marketing management. The approach used in this literature review is qualitative descriptive. The data collection technique is to use a literature study or to review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and is sourced from academic online media such as Thomson Reuters, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article are: 1) Consumer purchasing power plays a role in the marketing mix; 2) Competitors play a role in the marketing mix; 3) Consumer behavior plays a role in the marketing mix; and 4) Consumer demographics play a role in the marketing mix.